Educational Strategies for Enhancing Student Outcomes: Insights from Secondary Schools in Mbarara Municipality - Kobusiingye, Florah (Journal of Education and Practice, 2024)
Purpose: This paper examines the effectiveness of various educational strategies employed in secondary schools in Mbarara Municipality, Uganda, to enhance student outcomes. Methodology: The study uses a mixed-methods approach, combining quantitative data from standardized test scores with qualitative insights gathered through interviews with teachers, students, and school administrators. Findings: Findings reveal that student-centered teaching, regular formative assessments, and teacher professional development significantly improve student learning outcomes. However, challenges such as inadequate resources, overcrowded classrooms, and teacher absenteeism persist. Unique Contribution to Theory, Policy and Practice: Recommendations focus on enhancing stakeholder collaboration, improving teacher training, and leveraging technology for teaching and learning. These strategies have the potential to foster better academic performance and overall student development.